The mixed effects of a package of multilevel interventions on the health and care of pregnant women in Zinder, Niger - Sonja Y Hess; Cesaire T Ouedraogo; K Ryan Wessells; Rebecca R Young; Ibrahim Foungotin Bamba; M Thierno Faye; Ndiaye Banda (BMJ Global Health)
Background Anaemia is prevalent among pregnant women in rural Niger and antenatal care (ANC) attendance is suboptimal. We designed a programmatic intervention including community-based behaviour change communication, provision of essential drugs (including iron folic acid (IFA) supplements) and quality improvement activities at selected integrated health centres (IHCs).Objective To assess the impact of the programmatic intervention on: (1) utilisation of ANC, (2) adherence to daily IFA supplementation and (3) prevalence of adequate gestational weight gain (GWG) and anaemia among pregnant women in Zinder, Niger.Methods Using a quasi-experimental study design comparing a cohort of women at baseline to another cohort of women at endline, 18 IHCs and surrounding villages were randomly assigned to time of enrolment over 1 year. A baseline survey was implemented among randomly selected pregnant women in 68 village clusters. Subsequently, the intervention was rolled out and an endline survey was implemented 6 months later in the same villages.Results Mean age in the baseline (n=1385) and endline (n=922) surveys was 25.8±6.4 years. The percentage of pregnant women who reported attending any number of ANC and an adequate number of ANC for their gestational age, respectively, was not significantly different between the endline and the baseline surveys. Pregnant women in the endline survey were more likely to have received IFA (60.0% vs 45.8%, OR: 2.7 (1.2, 6.1)); and the proportion of pregnant women who reportedly consumed IFA daily in the previous 7 days was significantly higher in the endline than in the baseline survey (46.4% vs 32.8%, OR: 2.8 (1.2, 6.5)). There was no impact on the prevalence of adequate GWG or anaemia.Conclusions The programmatic intervention resulted in a modest increase in the number of pregnant women who reported receiving and consuming IFA supplements as recommended, but did not affect ANC attendance and nutritional status.